The genome sequence of the Crescent Plume, Marasmarcha lunaedactyla (Haworth, 1811) [version 1; peer review: 2 approved] - Douglas Boyes; Clare Boyes (Wellcome Open Research, 2023)
We present a genome assembly from an individual female Marasmarcha lunaedactyla (the Crescent Plume; Arthropoda; Insecta; Lepidoptera; Pterophoridae). The genome sequence is 771.1 megabases in span. Most of the assembly is scaffolded into 31 chromosomal pseudomolecules, including the W and Z sex chromosomes. The mitochondrial genome has also been assembled and is 16.43 kilobases in length. Gene annotation of this assembly on Ensembl identified 21,571 protein coding genes.